Not by Words Alone: Early Holocaust Graphic Narratives as a “Minor Art” - Perry, Rachel E. (Images, 2023)
Immediately after the Holocaust, scores of Jewish survivors created graphic narratives, in word and image, about their individual and collective wartime experiences under Nazi oppression. This essay will make a case for these early postwar works as a “minor art.” “Minor” captures the material characteristics of this low-capital, low-circulation printed matter: slight in weight, small in size, modest in price, and ephemeral in quality. It also describes their “poor” images that pull, in form and structure, from popular culture (comics, cartoons, illustrated books) on the margins of modernist concerns (composite image-texts relying on narrative storytelling). Borrowing from Gilles Deleuze and Félix Guattari’s concept of “minor literature” as a deterritorialized, political, collective utterance, I argue that disciplinary notions of “art” and “testimony” have prevented us from seeing this “minor art” and recognizing how its vernacular, amateur art practices allowed survivors to reconstruct the past, remember communities and identities erased, and reclaim their own narratives of persecution. Created by a minority (a decimated Jewish community) working on the peripheries of the art world, they tell a Jewish story using Jewish frames of reference to create a community outside of majoritarian culture. What is at stake in them is not only a poetics of recollection but a politics of representation: of seeing with Jews as a critical act by dominated persons against the dominant, antifascist master narrative of WWII and the primary media of its dissemination, photography and film. Ultimately, this “minor art” can have major implications for both how we understand the crucial first decade of survivor initiatives and how we write our histories of Jewish art.